An Unusual Complication of Chronic Suppurative Otitis Media: Bezold Abscess Progressing to Scapular Abscess - Pradhananga, Rabindra (International Archives of Otorhinolaryngology, 2014)
Introduction Suppurative otitis media is still the most common ear disease in developing countries. Otogenic complications of this disease have decreased considerably because of the advent of antibiotics, and few rare complications have been encountered.Objective To report a case of a patient with scapular abscess and lumber cellulitis that had progressed from Bezold abscess as a complication of squamous-type chronic suppurative otitis media.Resumed Report A 14-year-old girl presented with foul-smelling, purulent, left ear discharge of 1-year duration and decreased hearing on same ear of 6-month duration. She developed painful swelling in left side of neck with restricted neck movement and high-grade fever of 3-day duration and swelling over the left scapular area of 1-day duration. The examination and investigation diagnosed squamous-type chronic suppurative otitis media with Bezold abscess progressing to scapular abscess and lumber cellulitis.Final Comment Chronic suppurative otitis media can lead to abscess in any part of body.
Keywords: abscess; cellulitis; mastoiditis; suppurative otitis media